A novel design engineering review system with searchable content: knowledge engineering via real-time multimodal recording. (2nd December 2017) - Sivanathan, Aparajithan; Ritchie, James M; Lim, Theodore
ABSTRACT: Cradle to grave product support has been a key issue in the engineering sector over many years, particularly because product engineering legacy knowledge is often lost during the product development process unless rigorously captured in some way. This is particularly the case during formal design reviews at any point during a product's lifecycle where engineering changes are not fully documented or where salient but important aspects of decision making are difficult to document explicitly. Though many software systems are available to support design reviews, they have not necessarily met the expectations of industry. Consequently, traditional knowledge capture methods tend to be time-consuming, costly and disruptive leading to many companies simply giving up on this crucial aspect of product development. This paper presents research carried out with regard to prototyping and testing a potential knowledge engineering capture and reuse solution, demonstrating real-time user-logging using virtual design environments focused on team-based design 'reviews'. Called the Virtual Aided Design Engineering Review (VADER) system, it provides millisecond precision time-phased knowledge capture in an automatic and unobtrusive manner. Both structured and unstructured data are synthesised via a ubiquitous integration and temporal synchronisation (UbiITS) framework that enables interactive information mapping, retrieval and mining. VADER's frontend includes a virtual reality based 3D model view display as a multiuser collaborative interface and an auxiliary web interface for concurrent access by multiple distributed users during product design discussions. Feedback from engineers using the system demonstrated that this concept is one which believe would substantially enhance their engineering task knowledge capture, rapid retrieval and reuse capability. It was also surmised that, if required, such a system can be extended throughout the whole product development process capturing individual and team-based engineers' inputs across the whole cradle-to-grave product life cycle. Also, due to its generic nature, this approach is not limited only to engineering applications or virtual environments but can potentially be used in other sectors using computer-based technologies of any kind.